The Key Criteria in Deciding to Tender for Construction Projects - Bohari, A. A. M.; Ikau, R. A.; Budin, H.; Hadi, N. A.; Chan, V. S. L. (International Journal of Integrated Engineering, 2021)
Planning for a construction project is a formidable task which involves a huge investment with multiple stakeholders such as clients, consultants, and contractors. A tender is a submission of a technical, administrative, and contractual material made by a potential contractor in response to an invitation to tender by the project client. Established contractors normally realise the importance of doing initial research before committing themselves to enter the tender. Normally, tender pre-qualification is a strict process. A low-quality tender submitted due to problems such as insufficient time and incomplete tender documents normally lead to tender rejection by the client. Thus, this research aimed to provide a strategy to help the contractors in deciding whether they should or should not submit a tender at the initial tendering decision phase. The literature review was focused on the key factors identified in influencing the decision-making process and in the final part, the initial conceptual model was established